The Effectiveness of SETS based-learning in Improving Students’ Higher-Order Thinking Skills - Aulia Firdauzi Hasanah; Raharjo Raharjo; Fida Rachmadiarti (Universitas Islam Negeri Mataram, 2019)
The aim of this study was to investigate a SETS (Science, environment, technology) based-learning approach for junior high school students on how well SETS based-learning improves thinking skill on the waste management. This study was conducted to 20 students of 7th grade. Data collection were employed by class observation (carried out pre and post test), essay analysis (based on several cognitive indicators such as analyze, evaluate, and create), and learning activities regarding environmental issues. The results showed that SETS based-learning could positively improve students critical thinking in terms of learning process and performance in creativity, motivation, critical thinking. If the number of subjects is increase, SETS based-learning strategy could be more challenging.